Eine quantitative, landschaftsökologisch begründete Klassifikation von Bodenfeuchteregime-Typen für Mitteleuropa - Zepp, Harald (ERDKUNDE, 1991)
The characterization of soil moisture regimes is an important task within the scope of geoecology. The paper discusses existing spatially-orientated approaches and classifications of soil moisture regimes with reference to their geoecological significance. The proposed quantitative classification is adapted to Central and Western European conditions. It is based on many detailed field-measurements of soil water tension. The classification of the distribution function of soil water tension during the vegetative period is done with respect to plant ecology and hydrodynamics. By combining the moisture distribution classes of the top soil and of deeper horizons, uniform soil moisture regimes and those with a vertical gradation can be described adequately. Finally, the complementary concepts of soil moisture regimes and plant ecological moisture levels are discussed and the problems of regionalisation are exemplified.